PENERAPAN ADVANCED ENCRYPTION STANDARD UNTUK SISTEM LOGIN DAN REGISTRASI PADA SISTEM INFORMASI PENJUALAN (STUDI KASUS:TOKO ILHAM BANJAR) - Muldani Rachmat, Imam Fauzy (Insan Pembangunan Sistem Informasi dan Komputer (IPSIKOM), 2024)
Data security in sales information systems has become a critical priority in today's digital era. Ilham Banjar Store needs a system that can effectively protect user data, especially in login and registration features, which are vulnerable to security threats. The lack of encryption mechanisms in the current system results in user data, such as passwords, being transmitted in plaintext, increasing the risk of unauthorized access and data modification. Therefore, this study aims to enhance the security of the Ilham Banjar Store's sales information system by implementing the Advanced Encryption Standard (AES) 256-bit Cipher Block Chaining (CBC) method in the login and registration processes. The research method used is Research and Development (RD), consisting of stages such as literature review, needs analysis, system design, implementation, testing, evaluation, and analysis. The implementation of the Advanced Encryption Standard (AES) involves the encryption processes of AddRoundKey, SubBytes, ShiftRows, and MixColumns, and the decryption processes are the inverse of these encryption steps. Testing includes measuring encryption and decryption times as well as verifying data integrity using HMAC (Hash-Based Message Authentication Code). The research results show that the performance testing indicates encryption and decryption times remain within acceptable limits, and the encrypted and decrypted data maintain their integrity. Thus, the new system meets both security and performance requirements.